الموروث اللامادي الإسماعيلي في مجال كتامة الدعوة - بن النية رضا (University Of Eloued جامعة الوادي, 2023)
يندرج دخول أبي الله الشيعي إلى بلاد كتامة سنة 280 هـ/ 893م ضمن الإستراتيجية الجديدة التي عمدت إليها الحركة الإسماعيلية، عبر نقل دوائر نشاط دعاتها إلى مناطق الأطراف، بعد أن ضيّق الخلفاء العبّاسيون الخناق عليهم في المشرق، وامتد عمله الدعوي بأراضيها حتى أثمرت جهوده بتأسيس الدولة الفاطمية سنة 296 هـ/ 909م. وبالرغم من أنّ هذه الظرفية السياسية الجديدة قد استلزمت من داعي الإسماعيلية نقلةً بكامل ثقله إلى إفريقية، بيد أنّ طول فترة إقامته بمجال إيكجان، واحتكاكه المباشر بساكنته، قد ترك بصمة واضحة على كثير من عوائدها وسلوكاتها، امتدت ترسباتها لقرون طويلة. وضمن هذا السيّاق جاءت ورقتنا البحثية هذه التي تبحث في التاريخ المحلي لقبيلة كتامة في بُعده الاجتماعي، وتسعى استنادا إلى الرواية الشفوية، وصور من الثقافة الشعبية، معزّزة بما ظفرنا به من نصوص تاريخية شيعية وسنية، إلى سبر أغوار الموروث اللامادي الإسماعيلي في مجال إيكجان وأحوازه من حيث أصوله، وتجلياته، ومآلاته، ومستويات التفاعل المحلي معه. The coming of Obeid Allah, the Shiite, to the lands of Kutama in the year 280 AH /893 CE falls within the new strategy that the Ismaili movement has adopted, displacing their activities into the surroundings of the empire, after being oppressed by the Abbasid caliphs in the Orient. He had stepped up his effort, until he established the Fatimid caliphate in the year 296AH/ 909AD. The new politics required the Ismaili da’i to move with his full weight to Ifriqiya. However, the length of his stay in the area of Ikjan, and his direct contact with its inhabitants, left a clear imprint on many of its revenues and behaviors, the sedimentation of which extended for many centuries. Within the above context, the present research paper investigates the social dimension of the local history of the Kutama tribe. It seeks to dive into the depths of the Ismaili immaterial heritage in the region of Ikjan terms of its origins, aspects, current situation, and the levels of local interaction with it, based on the oral tradition, aspects of popular culture, as well as Shiite and Sunni historical texts.
قاعدة إيكجان وأحوازها أنموذجا
Keywords: التاريخ المحلي; كتامة; التراث اللامادي; إيكجان; الفاطميون; local history; Kutama; the immaterial heritage; Ikjan; the Fatimids